El estudio socio-histórico de las emociones y los sentimientos en las Ciencias Sociales del siglo XX - Leidy Bolaños Florido (Revista de Estudios Sociales, 2016)
This article presents a review of the main theoretical and thematic arguments that were developed in the social sciences, especially in sociology and anthropology, since the incorporation of emotions and sentiments as categories of socio-historical analysis throughout the course of the 20th century. It proposes a reflection on and a bibliographic analysis of the understanding of emotions in these disciplines at different moments of their development, based on the study of a selected group of authors. The guiding theme of the text is that the opening up of the social sciences to this type of studies began when certain authors distanced themselves from the classic dichotomies of the positivist tradition in order to establish the links among physical corporal elements, psychic habits, and the social and cultural forms underlying the study of society.